Taking the predators out of publishing - Hall, Robyn (My University, 2016)
In academic publishing, predatory publishing is an exploitative business model that involves charging publication fees to authors without providing the editorial and publishing services associated with legitimate journals (open access or not). Learn how to identify publishing predators and the techniques they use to engage you.
Presented on August 30, 2016 at Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: open access; academic publishing; journals; predatory publishing